Does Proactive Eco-Innovation Matter in the Energy Sector? - Toha, M.A. (Academic Conferences International Limited, 2021)
In recent times, eco-innovation has gained a lot of exposure in scholarly and business corporations due to its capacity to mitigate environmental and sustainability challenges. Eco-innovation can be categorized in two ways: proactive and reactive. Despite the significant investments and initiatives in eco-innovation, the world is still having environmental and sustainability issues. These environmental and sustainability issues are primarily experienced due to most of the firms seem to be reactive rather than proactive in their approach towards eco-innovation. Limited research has been conducted on proactive eco-innovation. Therefore, this study addresses this research gap by highlighting proactiveness. The aim of this research is to evaluate the proactive eco-innovation practices of the energy sector. This study focuses on the energy sector as this sector is considered the backbone of every emerging economy's future industrial and societal growth. Malaysia is the third-largest emerging country in Asia, whereby its primary economy is highly dependent on the energy sector. Therefore, this study focuses on 31 public listed energy firms in Malaysia using a secondary panel dataset. The existing index was adapted in conducting panel data collected from annual reports. (The year 2015-2019), sustainability reports and company websites. The data were analysed using SPSS and STATA software. The trend of proactive eco-innovation activities was investigated utilizing longitudinal analyses, emphasizing whether there is an upward or downward trend in the energy sector in terms of disclosing eco-innovation practices. Descriptive and correlation analysis was conducted by focusing on five prime dimensions of eco-innovation (product, process, technology, organizational, and marketing). The findings of this study would benefit academics through a proactive eco-innovation energy index based on secondary data. Further, the findings of this study will assist business corporations in formulating sustainable business plans towards eco-innovation. Â© 2021 Proceedings of the 17th European Conference on Management, Leadership and Governance, ECMLG 2021. All rights reserved.